The Men Who Would Be King: Moorish Political Hierarchies and Imperial Policy in Byzantine Africa. Issue 1 (2nd January 2021) - Merrills, Andy
ABSTRACT: Political hierarchies in the early medieval Maghrib have often been presented in schematic terms, and prominent leaders cast as 'kings' with little critical assessment of the implication of this language. The present study challenges this undifferentiated view of early Berber polities through the case study of early Byzantine Africa (c.535–565 CE): the best-documented period of early Berber history. It argues that hierarchies in this period were profoundly shaped by outside imperial authorities, both in modes of status display and in the language of authority. In Justinian's Africa, there was no place for local 'kings', but opportunities were created for new forms of social distinction, which may be traced in our sources. The article concludes with a discussion of modes of political distinction that may have developed in opposition to this imperial presence, and offers reflection for further study.